PELAKSANAAN SUPERVISI PENGAJARAN OLEH KEPALA SEKOLAH DI SMA - Bambang Abdul Mutalib; Zakaria Zakaria; Osa Juarsa (Manajer Pendididikan, 2017)
The general objective of this research was to describe the implementation of the supervision of the teaching by the head of in Public High School  1 Putri Hijau. This study is descriptive study. Subjects consisted of principals, teachers, and student. Data collection techniques are interview, documentation and observation.The results of this study show that: the work program supervision of teaching principals at Public High School  1 Putri Hijau, already has a draft for one year and redefined in the next year, engineering supervision of the implementation of the teaching of the Public High School 1 Putri Hijau carried out by an indirect approach and in Public High School 1 Putri Hijau carried out with the direct approach, and already  good family relationships among teachers